Chromosomal alterations in oral cancer for selected Indian and indigenous population / Noor Julieana Mat Amin - Noor Julieana, Mat Amin (2011)
Introduction: In the Malaysian population, the Indians were identified as having a higher oral cancer (OC) risk compared to Malays, Chinese and other ethnicities with betel quid chewing contributing the major factor among Indian female. Cancer progresses through a series of histopathological stages where the progression is thought to be driven by the accumulation of genetic alterations (Garnis et. al., 2009). Therefore, the identification of chromosomal alterations will not only enhance the understanding of the biology in this process, but will also identify important genes that might involve in oral carcinogenesis. Thus, this study utilised array Comparative Genomic Hybridization (arrayCGH) technology as a platform. Aims: To identify chromosomal alterations leading to the identification of genes involved in the development of OC, and to determine the relationship between selected altered regions with sociodemographic characteristics which include gender, ethnicity and habits and selected clinicopathological parameters namely tumour nodes metastasis (TNM) stage, tumour size (T), lymph node status (N), tumour grade and tumour site. Methods: A total of 20 fresh frozen tumour tissues diagnosed as OC and reference DNA from peripheral blood lymphocytes were obtained from the Malaysian Oral Cancer Data and Tissue Bank System (MOCDTBS)-Oral Cancer Research and Coordinating Centre (OCRCC), University of Malaya (UM). A series of 750 μm thick tissue sections were mounted in Optimal Cutting Temperature (OCT) compound and stained with H & E. Tissue sections containing more than 70% epithelial tumour were selected and confirmed by an oral pathologist. Analysis of arrayCGH was performed using the Human Genome CGH Microarray KIT 4x44K chip platform. Graphical iii overview of chromosomal alterations was obtained by using the Genomic Workbench Standard Edition 5.0.14. Validation of DUSP22 gene generated from arrayCGH results was then carried out at DNA (copy number) and cDNA (gene expression) levels. Statistical analysis was performed using SPSS version 19. Results: In this study, the occurrence of deleted regions was slightly higher than the amplified regions. The most frequently deleted regions were detected on chromosome 19p13.3, followed by 19p13-p13.11 and 19q13.3 while amplifications were most commonly detected at 8q24.3, 8q11.1-8q11.2 and 3q26 regions. The most common amplified gene detected was DUSP22, followed by KIAA0146. For the deleted regions, the most common genes detected were FBXO25, INPP5A, NKX6-2, C10orf92, CDH4, TAF4, and LSM14B. With respect to the clinicopathological parameters (tumour size (T), TNM stage, lymph node status (N), tumour grade and tumour site) and sociodemographic profile (gender, ethnicity and habits), no association was found between the most amplified (8q24.3, 8q11.1-8q11.2 and 3q26) and deleted regions (19p13.3, 19p13-p13.11 and 19q13.3). Only region 19p13-p13.11 showed significant relationship (p=0.044) with tumour site. Validation and analysis at copy number (CN) and gene expression (GE) level for the DUSP22 gene revealed consistent results with previous arrayCGH in which tumour cells showed over-expression. Conclusion: This study showed no association between chromosomal alterations and the clinicopathological parameters and sociodemographic profile studied. Only tumour site showed correlation with chromosomal alteration. It is recommended that a bigger study be conducted using bigger sample size in order to obtain more significant association.